Rodas de terapia comunitária: espaços de mudanças para profissionais da estratégia saúde da família - Morais, Fernanda Lúcia de Sousa Leite (2010)
The Community Therapy inserts in a political project context of services transformations and the health professionals practices. Considered a mental health action in the Basic Attention, the Community Therapy provides relief to emotional suffering through the share of life experiences, it contributes to the (re)meaning of life histories and promotes changes in its participants. Through this study, it was aimed to understand the changes happened in the personal and professional dimension in workers from Health Family Strategy with the involvement in the Community Therapy meetings. It is a qualitative study that resort to the methodological referential of Thematic Oral History. The research was accomplished at Sanitary District II, in the Municipal district of João Pessoa-PB, with eight health professionals from Health Family Strategies (ESF) that took part of Community Therapy meetings. In this study, the net was composed by eight Health Family Strategies professionals that took part, at least, of four Community Therapy meetings. The empiric material was produced through interview guided by questions and analyzed starting from the vital tone of collaborators' narrative accomplishing interface with the pertinent literature. The analysis allowed the construction of two thematic axes: Community therapy as developing space of learning, and, The Community Therapy meetings and the (re)meaning of professional practices. The analyzed material allowed to identify changes happened with the ESF professionals in their work process starting from the proportionate learning for the existences in the meetings. It can be considered the Community Therapy a potent strategy while care technology inserted in the Basic Attention in the construction perspective of community bases nets to solve ESF users or professionals conflicts.